Physiotherapy Students’ Perception on Learning through Smartphone: A Pilot Study - Balaraman, Thirumalaya (2015)
Objectives: Smartphone technology has transformed our lives in many ways and it is also reflected in learning. The objective of this pilot study was to find out the physiotherapy students’ perception on the use of smart phone and medical related applications (apps) as a learning tool in a private university in Malaysia. Methods: The method used in this study was an online survey. The link for the online survey form was posted on the Facebook page of the university Physio-Club and the participation in the survey was voluntary. The students have to answer close ended questions related to the ownership of the smart phone; frequency, duration and purpose of smart phone and medical related apps use for their learning, in university and clinical environment. Open ended questions were also used to explore the students’ perception about the usefulness of the applications, and their recommendations. Results: 68 students responded to the questionnaire of which 69.1% and 30.9% were female and male students respectively. Google Android was the most popular among the students (61.8%) followed by iPhone (25%). The majority (63.2%) of the students possessed 1to5medical related apps in their Smartphone. Their preferred use was, for educational learning (79.4%) and revising (74.6%), with less usage in clinical ward (30.2%) and clinic (20.6%) environment. Their usage frequency was once or twice a day with duration lasting between1and10minutes, in university as well as in a clinical environment. They often used the smart phone and applications to find out the disease diagnosis/ management and they found it most useful due to easy accessibility of information. Conclusion: This pilot study showed that most of the physiotherapy students use medical related apps in their Smartphone for learning activity, and they mostly recommended dictionary and physiotherapy apps.